Eco-morphological convergence among Neotropical deer - Oliveira, Márcio Leite de; Grotta-Neto, Francisco [UNESP]; Peres, Pedro Henrique de Faria [UNESP]; Caparroz, Renato; Duarte, José Maurício Barbanti [UNESP] (Oxford University Press (OUP), 2025)
Adaptative convergences of ecomorphological traits are widespread in several animal lineages. Among Neotropical deer there are very similar species characterized by a set of homoplasies: small body sizes, spiked antlers, and front legs shorter than the rear legs. These species are in different phylogenetic clades among larger and branched-antlered sympatric species, which are considered ancestral traits. It is hypothesized that the convergence of these morphological traits is an adaptation to living in dense forests. This study tested whether the spiked-antlered species are more associated with forest environments compared with branched-antlered species, which antler type—spike or branched—represents the ancestral morphotype, and if there is a correlation between phylogenetic distance (PD) and ecological difference (ED) in this species group. We found that spiked-antlered species had a more significant association with forest environments than branched-antlered species, with the latter morphotype being associated with higher body mass. Our ancestral state reconstructions indicate the branched-antlered morphotype as the ancestral trait. The correlation between PD and ED was weak in this group. The evolutionary pathway of this antler morphology underscores the remarkable plasticity of this trait in Neotropical deer.
Keywords: adaptative convergence; evolution; mammals; Neotropical realm; phylogenetic distance